Single-cell and spatial transcriptomics in endocrine research - Ryusaku Matsumoto; Takuya Yamamoto (Endocrine Journal)
Accumulating evidence suggests that cellular heterogeneity in organs and cell-cell and tissue-tissue interactions are crucial for maintaining physical homeostasis and disease progression. Endocrine organs also exhibit cellular heterogeneity and comprise multiple cell types. For instance, the pituitary gland comprises five types of pituitary hormone-producing cells as well as non-hormone-producing supporting cells, such as fibroblasts, endothelial cells, and folliculostellate cells. However, the functional roles of the interactions between hormone-producing and non-producing cells in the pituitary gland remain incompletely understood. Over the past decade, emerging technologies such as single-cell and spatial transcriptomics have provided excellent tools for studying cellular heterogeneity and their interactions; however, the application of these technologies in endocrine research remains limited. This review provides an overview of these technologies and discusses their strengths and limitations. Additionally, we also summarize the potential future applications of single-cell and spatial transcriptomics in the study of endocrine organs and their disorders.